RECENT EUROPEAN GUIDELINES FOR THE MANAGEMENT OF ARTERIAL HYPERTENSION (2007): WHAT IS NEW IN APPROACH TO CHOICE OF DRUG? - S. Y. Martsevich (Столичная издательская компания, 2015)
Recent European Guidelines for the Management of Arterial Hypertension (2007): what is new in approach to choice of drug?